Analisis Keluhan Pengguna pada Aplikasi Layanan Kesehatan Berbasis Text Mining - Nur Laily Haryanti; Sayyidah Maulidatul Afraah; Ratih Dianingtyas Kurnia (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2026)
The digital transformation of healthcare in Indonesia has led to the emergence of services like Mobile JKN to improve access and service efficiency. However, ongoing user complaints regarding ease of access and system reliability indicate the need for user experience-based evaluation. This study aims to identify user complaint patterns, evaluate the ease of application access, and formulate recommendations for improvements to enhance the quality of digital public services in the healthcare sector, particularly the Mobile JKN application. This study uses a text mining approach to user reviews on the Google Play Store, referring to software quality characteristics based on the ISO/IEC 25010 standard. The research process was carried out through several stages, starting from data collection (scraping), preprocessing and text cleaning, review filtering based on keywords related to performance and satisfaction, and sentimen analysis to understand user perceptions more comprehensively. The results of word frequency analysis and word cloud visualization indicate that the most dominant user complaints are related to security and access control, particularly related to login problems and OTP verification failures that hinder service access. On the other hand, this application demonstrates excellence in performance efficiency, particularly the online queuing feature which is considered fast, practical, and helps users save time. Based on a SWOT analysis, this study recommends strengthening the authentication system infrastructure and improving data synchronization to minimize access barriers and increase user trust. These findings are expected to serve as a strategic reference for digital healthcare managers in improving service quality, user retention, and community satisfaction in a sustainable manner.